Debtor Protection If Online Loan Crime Occurs - Kodradjaja, Fenny; Cornelis, Vieta Ilmelda; Astutik, Sri (Ipso Jure, 2025)
Popular peer-to-peer lending fintech is also called online lending. As an innovation in the financial sector, online loans offer financial assistance to people in need and applying for loans is quite easy. Online lenders as financial service providers are regulated by the Financial Services Authority, which is an institution legally authorized to regulate, supervise, audit and investigate the financial services sector. However, in practice, online loan management in Indonesia often causes problems even though it is regulated and supervised by the OJK. These problems are related to personal data breaches, resolving intimidation, and several other problems. The purpose of this research is to find out what the legal regulations for online loans are in Indonesia and what legal protection is given to borrowers who make online loans through legal regulations in order to avoid problems related to online loans. This research uses normative legal research methods, the approach used is a legal approach. The results of this research show that the basis for regulating online loans is in OJK Regulation Number 10/POJK.05/2022 concerning Technology-Based Community Financing Services. The legal protection for online borrowers is divided into preventive protection, namely protection against criminal acts, and contains prohibitions on online borrowing. And law enforcement protection to resolve disputes that arise, support through out-of-court dispute resolution tools, the Alternative Financial Services Sector Dispute Resolution Institute (LAPS SJK) and legal defense of debtor interests by assisting in the initiation of legal efforts